Penerapan Model Cooperative Learning Tipe STAD pada Materi Indonesiaku Kaya Budaya untuk Meningkatkan Hasil Belajar Siswa di SDK Wanno Badu - Jarang, Nelson Tidi; Lende, Petrus; Lede, Yulius Keremata; Daga, Agustinus Tanggu (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to improve the learning outcomes of fourth-grade students at SDK Wanno Badu. This type of research is Classroom Action Research (CAR). The subjects of this study are fourth-grade students at SDK Wanno Badu, totaling 17 students, comprising 9 female students and 8 male students. Data were collected through (1) learning outcome tests, observation, and documentation. Data analysis was carried out using descriptive quantitative and qualitative methods. The results of the observation of teacher activities in managing learning for each cycle, taking into account the average achievement, continued to show an increase from cycle I to cycle II. The teacher activity observation score in cycle I was 80.35, which falls into the good category. In cycle II, there was an increase to 98.21, which is in the very good category. The very good achievement in cycle II indicates that the activities in managing learning to improve student learning outcomes using the STAD-type cooperative learning model were highly effective. The observation results on the students also showed an improvement, namely in cycle I the average score reached 76.78 with a good criterion, and in cycle II it increased to 93.74 with an excellent category. From this research, it was found that in cycle I the average percentage score was 71.76% and the classical completeness was 58.82%, and in cycle II the average percentage score was 84.11% and the classical completeness was 88.23%.